Dinuclear Copper Intermediates in Copper(I)‐Catalyzed Azide–Alkyne Cycloaddition Directly Observed by Electrospray Ionization Mass Spectrometry1. (22nd January 2015) - Iacobucci, Claudio; Reale, Samantha; Gal, Jean‐François; De Angelis, Francesco
Abstract The mechanism of the CuAAC reaction has been investigated by electrospray ionization mass spectrometry (ESI‐MS) using a combination of the neutral reactant approach and the ion‐tagging strategy. Under these conditions, for the first time, putative dinuclear copper intermediates were fished out and characterized by ESI(+)‐MS/MS. New insight into the CuAAC reaction mechanisms is provided and a catalytic cycle is proposed.